Regulation and Effect of Taurine on Metabolism - Miyazaki, Teruo; Ito, Takashi; Baseggio Conrado, Alessia; Murakami, Shigeru (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Taurine (2-aminoethanesulfonic acid) has been reported to have a lot of physiological and pharmacological functions in various tissues, cells, and organelles in many species since discovered in the gall bladder of bovine in 1827, and its novel functions and roles have now been focused in many fields. This Special Issue consisted of eight original and two review articles contains the newest findings on the roles of taurine as an essential nutrient for development and growth in fetuses and infants, and functional maintenance in the brain, skeletal muscles, and others in adults, in mammalian, chicken, and fish.